2017
DOI: 10.1371/journal.pone.0170317
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Enrichment Blunts Ethanol Consumption after Restraint Stress in C57BL/6 Mice

Abstract: Elevated alcohol intake after abstinence is a key feature of the addiction process. Some studies have shown that environmental enrichment (EE) affects ethanol intake and other reinforcing effects. However, different EE protocols may vary in their ability to influence alcohol consumption and stress-induced intake. The present study evaluated whether short (3 h) or continuous (24 h) EE protocols affect ethanol consumption after periods of withdrawal. Mice were challenged with stressful stimuli (24 h isolation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 51 publications
2
20
0
Order By: Relevance
“…Importantly, some recent studies have shown that social and EE reduces EtOH preference and binge-like EtOH drinking in adult male C57BL/6 mice as measured by a modified, 2BC, DID task. Thus, C57BL/6 mice living in continuous (24 h) or restricted (3 h) EE conditions consumed less EtOH than control mice over 24 h in a DID-2BC procedure after acute stressful conditions (Marianno et al, 2017 ), and C57BL/6 mice group-housed for 40 days immediately after weaning showed lower binge-like EtOH drinking in a DID-2BC task than isolated-housed mice during the same developmental period (Lopez et al, 2011 ). Moreover, providing EE was sufficient to counteract high binge-like EtOH intake triggered by chronic social isolation in C57BL/6J mice (Lopez and Laber, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, some recent studies have shown that social and EE reduces EtOH preference and binge-like EtOH drinking in adult male C57BL/6 mice as measured by a modified, 2BC, DID task. Thus, C57BL/6 mice living in continuous (24 h) or restricted (3 h) EE conditions consumed less EtOH than control mice over 24 h in a DID-2BC procedure after acute stressful conditions (Marianno et al, 2017 ), and C57BL/6 mice group-housed for 40 days immediately after weaning showed lower binge-like EtOH drinking in a DID-2BC task than isolated-housed mice during the same developmental period (Lopez et al, 2011 ). Moreover, providing EE was sufficient to counteract high binge-like EtOH intake triggered by chronic social isolation in C57BL/6J mice (Lopez and Laber, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to improving psychological and physiological well-being in otherwise healthy animals, EE may limit behavioral, cognitive and biological disturbances provoked by stressful experiences. For instance, EE reduced anxiety-like behaviors and prevented cognitive impairments ordinarily elicited by acute and chronic stressors (Cordner and Tamashiro, 2016 ; Bahi, 2017 ; Marianno et al, 2017 ; Dandi et al, 2018 ). Mice housed in EE also exhibited limited corticosterone elevations and neuronal activation after stressor exposure (Branchi et al, 2013 ; Reichmann et al, 2013 ; Mesa-Gresa et al, 2016 ), indicating that housing conditions may modulate the impact of external stressors on hormonal and brain functions.…”
Section: Introductionmentioning
confidence: 99%
“…Other work, however, reported lower ethanol consumption and lower ethanol-induced CPP after EE in rats that were selected for high ethanol preference 19 or spontaneous hypertension 20 . More recent studies demonstrated that EE decreased ethanol consumption after restraint stress 21 and that EE blocked the development and expression of ethanol-induced behavioral sensitization in peri-adolescent Swiss mice 12 . EE also decreased BDNF levels in the PFC, but not in hippocampus.…”
Section: Introductionmentioning
confidence: 99%